(untitled) - Kirkwood, Niall (Hoboken, N.J., 2004)
Weatering and Durability in Landscape Architecture provides authoritative guidelines to weathering, durability, and physical changes in the designed landscape over time. Provides innovative weathering strategies illustrated with case studies.Includes information on completed landscapes with data and commentary on maintenance and durability. Provides the personal weathering and durability strategies of leading experts.
Keywords: Kiến trúc cảnh quan,Thiết kế cảnh quan